Long-term survival with anlotinib as a front-line treatment in an elderly NSCLC patient: A case report - Wang, Jingyi; Li, Xiaoqing; Zhou, Juan; Qiu, Dan; Zhang, Mengyao; Sun, Lan; Li, Shengwen Calvin (Frontiers in Oncology, 2023)
BACKGROUND: Half of non-small cell lung cancer (NSCLC) patients are older than 70 years who have limited therapeutic options due to poor tolerance and being excluded in most clinical trials. Anlotinib hydrochloride, a novel oral multitarget tyrosine kinase inhibitor, has been approved for the standard third-line treatment of NSCLC in China. Herein, we report an elderly NSCLC patient without any driver-gene mutations undergoing anlotinib as a front-line treatment achieved a long-term survival. CASE SUMMARY: The 77-year-old male patient was admitted to the hospital for chest tightness after activity for 1 week. The patient was diagnosed with stage ⅢB driver-gene-negative squamous cell lung carcinoma. Thereafter he was treated with anlotinib for 2 years and 10 months from the first diagnosis to the last disease progression (PD). Briefly, anlotinib combined with platinum-based chemotherapy was performed as the first-line therapy over 6 cycles. After 6 more cycles of anlotinib monotherapy maintenance, disease progression occurred. Then anlotinib combined with tegafur was administered as a salvage treatment, and disease was controlled again. After 29 cycles of anlotinib combined with tegafur regimens, the disease progressed lastly, and the patient achieved totally 34 months of progression-free survival (PFS) after anlotinib as the front-line treatment, and he is still alive with a good performance status now. CONCLUSION：As a front-line regimen, anlotinib achieved a long-term survival in this patient.